The Influence of Tarbawi Tafsir in the Formation of Noble Morals in Middle Schools - Elin Solihatin; Iskandar Mirza (Penerbit Hellow Pustaka, 2024)
Tafsir Tarbawi has a significant influence on the formation of noble morals in secondary schools. Through a deep understanding of the teachings of the Qur'an, students can internalize moral values that are very important for the development of their character. In this way, tarbawi interpretation not only becomes an educational tool, but also a guide to life for students in facing various challenges in an increasingly complex world. However, challenges in implementing tarbawi tafsir in secondary schools remain. Lack of understanding and resources for educators is an obstacle that must be overcome. Therefore, it is important for schools and educational institutions to provide adequate training for educators so that they can teach tarbawi tafsir more effectively. With good training, educators can be more confident in conveying moral values to students. This paper emphasizes that the formation of noble morals through tarbawi interpretation is an effort that is not only important, but also urgent amidst the moral challenges faced by teenagers today. With the right approach, it is hoped that tarbawi interpretation can become an effective tool in creating a generation that is intelligent, responsible and has noble character.